Rancang bangun aplikasi berbasis augmented reality dengan tema alat musik tradisional Indonesia sebagai media pembelajaran di sekolah dasar - Annisa Puspita; Ari Andrean; Farhan Fathurrohman Fauzi (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2021)
Currently learning is done online. So that the quality of the teaching and learning process does not decrease, teachers must innovate in learning by utilizing information and communication technology. This study aims to create an augmented reality-based application with the theme of traditional Indonesian musical instruments that can be used as learning media on theme 1, sub-theme 1, learning 1, in grade 4 elementary school. The method used in this research is the Multimedia Development Life Cycle and the Literature Study method. The result of this research is an augmented reality-based interactive learning application that can be used on the android platform, along with a boardgame which is an additional component of the application. The application is distributed to a non-governmental organization called Rumah Pelangi Indonesia, and the 090 Cibiru State Elementary School which will later be used as learning media for students there.